Mature osteoblasts in human non-union fractures express collagen type III. Issue 4 (August 1997) - Lawton, D M; Andrew, J G; Marsh, D R; Hoyland, J A; Freemont, A J
Abstract : AIMS: High levels of collagen type III are biochemically detectable in biopsies of non-uniting fractures, and in the serum of patients suffering from this condition. The aim of this study was to determine whether the expression of collagen type III was limited to fibrous tissue in non-unions, or whether some was present in bone. METHODS: Biopsies from normally healing human fractures and non-unions were examined using in situ hybridisation and immunohistochemistry. RESULTS: The mesenchymal cell population, which includes fibroblast and osteoblast precursors, expressed mRNA for collagen type III. However, mature osteoblasts on the surface of woven bone varied profoundly between normally healing fractures (in which they were negative or occasionally weakly positive) and non-unions (in which they were strongly positive). Areas of woven bone that had osteoblasts positive for collagen type III mRNA also immunostained positively for the protein. CONCLUSIONS: This study shows that non-union fracture callus osteoblasts on the surfaces of woven bone exhibit an unusual phenotype: they express collagen type III, a molecule characteristic of an earlier stage of osteoblast differentiation, which is not expressed by osteoblasts on woven bone surfaces of bone that develops normally. This finding may be useful in developing an early clinical test for impending non-union.